Analisis Faktor Dominan yang Mengakibatkan Pembengkakan Biaya oleh Kontraktor pada Proyek Jalan Kabupaten Wonogiri APBD Tahun 2017 dan 2018 - Muhammad Nur Sahid; Anto Budi Listyawan; Abdul Rochman; Rim Dzaky Haidar Rim (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
The implementation of the road project in Wonogiri Regency was often different between the planning with has be held that making problem for contractor like as late work and cost overrun. Therefore, the purpose of this research is knowing what is cost overrun factors and also amount of cost overruns of the road project in Wonogiri Regency which used APBD 2017 and 2018 experienced by contractor. This research was conducted by asking questions to the contractor who worked on the road project in 2017 and 2018. The analysis of this research has using the SPSS program. Based on the analysis has been done, field regulation become dominant of cost overrun. The lack of provision of field support facilities and the limited size of the project area are the reasons why field regulation factors can be a major factor causing cost overruns on road projects in Wonogiri Regency. Based on the answers from respondents it can be concluded that the contractors who experienced a swelling cost of 1% -5% there were 44 respondents, then for the cost swelling of 6% -10% there were 28 respondents, and 11% -15% there were 2 respondents, and 16% -20% only 1 respondent.